Hak dan Kewajiban Krama Desa terhadap Karang Desa di Desa Adat Tumbu Karangasem - Putu Aditya Palguna Yoga; I Made Suwitra; I Ketut Sukadana (Fakultas Hukum, Universitas Warmadewa, 2021)
The relationship between the ruler and the land is closely related to obligations in the form of ayahan for village karma for both the banjar and the village. This study aims to determine the control of village coral and the legal consequences if there is village karma that neglects its obligations. The research method used in this research is empirical legal research with a conceptual approach. Data that has been collected through interview techniques. The results of this study indicate that the right for village krama who has carried out their obligations is to legally obtain Karang Desa land protected by the village. If Krama Desa dies, he will receive land. Meanwhile, the obligation of the village manners who occupy the village reef is obliged to take part in the village temple during the odalan fee in the form of pepesan money (klangsah palpalan penjor) and must be present at the time of mutual cooperation activities. Through this research, it is hoped that the village officers will socialize more often about Karang Desa, especially regarding their rights and obligations so that one day the Krama Desa who violates them will not be given sanctions.